FRI0393 Predictive value of history of digital ulcers in a eustar cohort of patients with systemic sclerosis. (23rd January 2014) - Mihai, C.; Landewé, R.; van der Heijde, D.; Walker, U.; Constantin, P. I.; Ionescu, R. M.; Rednic, S.; Gherghe, A. M.; Sfrent-Cornăteanu, R.; Allanore, Y.; Avouac, J.; Czirjak, L.; et al.
Abstract : Background: Digital ulcers (DUs) have a prevalence of up to 36% in systemic sclerosis (SSc) patients and are a heavy burden, significantly reducing quality of life and function and leading to severe complications. Objectives: To evaluate in SSc patients the hypothesis that a history of DUs at presentation may be a predictor of vascular outcomes and of overall clinical worsening and death. Methods: All patients from the EUSTAR database (MEDS online), satisfying the 1980 ACR classification criteria for SSc, who had a follow-up of at least 3 years since inclusion or who have died, were included in the analysis. History of DUs at presentation as a predictor of disease progression or death was evaluated by univariate and multivariate Cox proportional hazard regression analysis. Results: 3207 patients matched the inclusion criteria (age at inclusion 54.6±13.6 years, disease duration since the onset of first non-Raynaud's symptom: 8.1±7.7 years and from onset of Raynaud's phenomenon (RP) 12.3±11.2 years, male sex 13.2%, 33.4% diffuse subset, 96.4% presenting RP). At presentation, 1092 patients had a history of DUs (34.1%). DU history at baseline was the strongest predictor for the presence of active DUs at prospective visits, with a hazard ratio (HR, 95% confidence interval) of 2.55 (2.02-3.20), p<0.001 when adjusting for age, gender and all parameters found significant in univariate analysis (elevated systolic pulmonary arterial pressure by ultrasound (sPAP-US), decreased carbon monoxyde lung diffusion (DLCO), anti-Scl70 antibodies). In univariate age-adjusted analysis, DUs were predictive of severe interstitial lung disease, defined as a forced vital capacity (FVC) of <50% predicted: HR 1.75 (1.59-2.65), p<0.01, and for severely decreased DLCO (<40% predicted), HR 1.47(1.22-1.76), p<0.001, but in multivariate analysis this association was not statistically significant anymore. There were 453 deaths recorded. The mean±SD time to death since RP onset was 17.3±11.3 years and since first non-Raynaud symptom 8.9±8.6 years. DUs were found to be predictive for death (HR 1.50, (1.15-1.96), p<0.001) after adjusting for age, gender and all baseline parameters found to be significantly associated in the univariate analysis (disease subset, elevated sPAP-US, proteinuria, significant dyspnea, decreased FVC and DLCO, history of renal crisis and presence of anti-Scl70 antibodies). Conclusions: A history of DUs at presentation is a predictor for the presence of DUs at follow-up and forecasts early mortality in patients with SSc. As such, the presence of DUs in a patient with SSc predicts a poor outcome. Disclosure of Interest : None Declared